Hydraulics and pneumatics a technician's and engineer's guide - Parr, E. A. (E. Andrew)
Nearly all industrial processes require objects to be moved, manipulated or subjected to some sort of force. This is frequently accomplished by means of electrical equipment (such as motors or solenoids), or via devices driven by air (pneumatics) or liquids (hydraulics). This book has been written by a process control engineer as a guide to the operation of hydraulic and pneumatic systems for all engineers and technicians who wish to have an insight into the components and operation of such a system. This second edition has been fully updated to include all recent developments such as the incr.